Descrição do processo de negociação coletiva intermediado pela Mesa Municipal de Negociação Permanente (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Description of the collective negotiation process brokered by the Municipal Permanent Negotiation Board